Conventional and phenomics characterization provides insight into the diversity and relationships of hypervariable scarlet (Solanum aethiopicum L.) and gboma (S. macrocarpon L.) eggplant complexes - Plazas, Mariola; Andújar, Isabel; Vilanova, Santiago; Gramazio, Pietro; Herraiz, F. Javier; Prohens, Jaime (Frontiers in Plant Science, 2014)
Scarlet (Solanum aethiopicum) and gboma (S. macrocarpon) eggplants are major vegetable crops in sub-Saharan Africa. Together with their respective wild ancestors (S. anguivi and S. dasyphyllum) and intermediate cultivated-wild forms they constitute the so-called scarlet and gboma eggplant complexes. We used conventional descriptors and the high-throughput phenomics tool Tomato Analyzer for characterizing 63 accessions of the scarlet eggplant complex, including the four S. aethiopicum cultivar groups (Aculeatum, Gilo, Kumba, and Shum), Intermediate S. aethiopicum-S. anguivi forms, and S. anguivi, and 12 cultivated and wild accessions of the gboma eggplant complex. A large diversity was found between both complexes, showing that they are very well differentiated from each other. Within the scarlet eggplant complex, many significant differences were also found among cultivar groups, but more differences were found for fruit traits evaluated with Tomato Analyzer than with conventional descriptors. In particular, Tomato Analyzer phenomics characterization was useful for distinguishing small fruited groups (Shum, Intermediate, and S. anguivi), as well as groups for which few or no significant differences were observed for plant traits. Multivariate principal components analysis (PCA) separated well all groups, except the Intermediate group which plotted between S. anguivi and small fruited S. aethiopicum accessions. For the gboma eggplant complex, S. dasyphyllum was clearly distinguished from S. macrocarpon and an important diversity was found in the latter. The results have shown that both complexes are hypervariable and have provided insight into their diversity and relationships. The information obtained has important implications for the conservation and management of genetic resources as well as for the selection and breeding of both scarlet and gboma eggplants.